Positional isomer differentiation of synthetic cannabinoid JWH‐081 by GC‐MS/MS. (20th February 2015) - Kusano, Maiko; Zaitsu, Kei; Nakayama, Hiroshi; Nakajima, Junichi; Hisatsune, Kazuaki; Moriyasu, Takako; Matsuta, Shuntaro; Katagi, Munehiro; Tsuchihashi, Hitoshi; Ishii, Akira
Abstract : Like many new designer drugs of abuse, synthetic cannabinoids (SC) have structural or positional isomers which may or may not all be regulated under law. Differences in acute toxicity may exist between isomers which impose further burden in the fields of forensic toxicology, medicine and legislation. Isomer differentiation therefore becomes crucial from these standpoints as new designer drugs continuously emerge with just minor positional modifications to their preexisting analogs. The aim of this study was to differentiate the positional isomers of JWH‐081. Purchased standard compounds of JWH‐081 and its positional isomers were analyzed by gas chromatography‐electron ionization‐mass spectrometry (GC‐EI‐MS) first in scan mode to investigate those isomers who could be differentiated by EI scan spectra. Isomers with identical or near‐identical EI spectra were further subjected to GC‐tandem mass spectrometry (MS/MS) analysis with appropriate precursor ions. EI scan was able to distinguish 3 of the 7 isomers: 2‐methoxy, 7‐methoxy and 8‐methoxy. The remaining isomers exhibited near‐identical spectra; hence, MS/MS was performed by selecting m/z 185 and 157 as precursor ions. 3‐Methoxy and 5‐methoxy isomers produced characteristic product ions that enabled the differentiation between them. Product ion spectrum of 6‐methoxy isomer resembled that of JWH‐081; however, the relative ion intensities were clearly different from one another. The combination of EI scan and MS/MS allowed for the regioisomeric differentiation of the targeted compounds in this study. Copyright © 2015 John Wiley & Sons, Ltd.